A Survey on the position classification and salaries of librarians in special libraries in Metro Manila a follow-up study. - Oliva, Kathleen T. (2004)
In 1987, a survey on the position classification and salaries of librarians in special libraries in Metro Manila was done by a project team from the Institute of Library Science in the University of the Philippines Diliman. However, many changes have brought transformations in special libraries and librarians in the past years. With these changes, do the findings of the ILS survey still hold true today?.